Perinatal Outcome of the Second Twin - Joshi, R; Baral, G (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: The purpose of this study was to determine the perinatal outcome of the second twin compared to the first one. Methods: This is a hospital based comparative study of 60 pregnant women with twin pregnancy at Paropakar Maternity and Women’s Hospital, Kathmandu from 14 January 2013 to13 April 2013. Apgar score and admission to neonatal intensive care unit of the first and the second twins were studied in relation to the gestational age, chorionicity, mode of delivery, inter-delivery interval and birth weight. Mc Nemars test was used with 0.05 as the level of significance. Results: Among 60 sets of twins, Apgar score of the second twin was found to be lower than the first one (p=0.02) in general and in preterm gestation (p=0.049), dichorionic diamniotic chorionicity (p=0.012), vaginal delivery (p<0.001), inter-delivery interval of <30 minutes (p=0.007) and birth weight discordance of <30 % (p=0.014). Admission to neonatal intensive care unit was not significant (p=0.5). Conclusions: Second twin had low Apgar score and the neonatal admission rate was similar for both twins.